PENATAAN KEWENANGAN (URUSAN) PEMERINTAHAN DESA DAN PENGEMBANGAN STANDAR PELAYANAN MINIMAL (SPM) - dan Andi Wahyudi, Tri Widodo W. Utomo (Pusjar SKPP Lembaga Administrasi Negara, 2008)
Village government knows much about grass root problems because it’s the lowest level government and the most familiar government to the village people. The existence of village had been known even far before Indonesia was built. But in fact, village development runs slowly and far away behind the city, even more for the villages which located in the remote area. The Village government isn’t sub-ordinate of district government so it needs an authority given by the district government. So far, the village government only do administrative activities i.e. serve recommendation letter to people. By giving more authorities to the village government, it will bring advantages for the grass root people and improve villager’s live. As the function of government is to serve people, village government needs an instrument to make it more effective. Implementing the Standard of Minimum Service (Standar Pelayanan Minimal/SPM) at the village government is an alternative way to fulfill people constitutional rights in getting government services. The Standard of Minimum Service is derived from the Law Number 32/2004 and this instrument is used for province and district government. However, the village government is able to adopt this instrument and it also needs an empowerment on the organizational, financial and human resources aspects unto the village government. Keywords : Authority, Village Government, Minimal Service Standard